Perkembangan Motorik Halus Anak dengan Kegiatan Menyusun Puzzle Geometri pada Usia 3-4 Tahun di KB Al-Ishlah Gorontalo - Sri Ramla Wati Monoarfa; Rabiatul Adawiya Lapasu; Prahara M. Marjuni; Tri Hastri Bumulo; Annisa Fahmi Mannassai (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This research aims to determine the development of fine motor skills in children aged 3-4 years through the activity of compiling geometric puzzles at Kbit Al-Ishlah, Gorontalo City. This research is classroom action research at KBIT Al-Ishlah. The subjects in this study were 9 children, consisting of 5 boys and 4 girls aged 3-4 years at Kbit Al-Ishlah Gorontalo. The data collection technique used qualitative description techniques. The results of this study showed that there was an increase in the fine motor skills of children aged 3-4 years through the activity of putting together puzzles. It can be explained that fine motor skills in children at KBIT Al-Ishlah are the child's ability to use the fingers of the right and left hand in the activity of compiling geometric puzzles, 5 out of 9 children or 75% of children are able to develop as expected, 2 children 10% of children The ability is starting to develop, while 1 child 5% is at the ability not yet developed. Most of the children show good mastery of fine motor skills as measured through the activity of putting together geometric puzzles, although there is still one child who needs more attention.